If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(80 + -1x) = 816 (80 * 12 + -1x * 12) = 816 (960 + -12x) = 816 Solving 960 + -12x = 816 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-960' to each side of the equation. 960 + -960 + -12x = 816 + -960 Combine like terms: 960 + -960 = 0 0 + -12x = 816 + -960 -12x = 816 + -960 Combine like terms: 816 + -960 = -144 -12x = -144 Divide each side by '-12'. x = 12 Simplifying x = 12
| 2+5+x=3+4 | | 19-x-5=30 | | (25b-6)-8(3b+3)=-7 | | 8+3(-2n-7)=-(-5-3n) | | (x+4)(3x-24)=0 | | 7(b-5)=72 | | 18+-6g=-12g | | 3px(-3)=36 | | -2(-6x-4)=8x+2(x-2) | | 3(14+-5y)-5y=10 | | Y-15x=16 | | 2(1-x)+5=3(1+x)-8 | | -6(r+8)=-96 | | 5+3(-2g-7)=-40 | | -5-4p=27 | | y(2y+4)=77 | | x+15=65 | | -10-4p=22 | | 3x+5=6x-28 | | a-8=17 | | 45p+10q= | | 5(1+2p)=7p-1 | | -15-3p=6 | | 7+4b=4(1+b)+3 | | r+16=44 | | -5g+(8-g)=12 | | -47-7m=2 | | 3x^2-7x+12.25=13.25 | | m+1+5=0 | | -5x^2+7x+2=0 | | -42-6m=-12 | | 21g-12=98 |